Preserved circannual rhythm of vitamin D in kidney transplant patients (Swiss Medical Weekly, 2012)
BACKGROUND: A high prevalence of vitamin D insufficiency has been found in the general population, in patients with chronic kidney disease and in kidney transplant patients. During winter there is a higher prevalence of vitamin D insufficiency due to the lack of solar ultraviolet B (UVB) exposure. Kidney transplant patients are advised to avoid sun exposure because of their high risk of skin cancer. This is considered to be one of the main reasons for the very high prevalence of vitamin D insufficiency in these patients. Whether circannual rhythm of vitamin D is totally reversed in kidney transplant patients is not known. METHODS: In this single centre prospective observational study, 50 kidney transplant patients visiting our outpatient clinic in January and February 2011 were included. Serum concentration of 25-hydroxvitamin D (25[OH]D), 1-25-hydroxvitamin D (1-25[OH]D) and intact parathormone (iPTH) were measured at study entry and 6 months later in summer. RESULTS: A total of 90% (45/50) of the study population had vitamin D deficiency 25(OH)D (